2022
DOI: 10.1007/s10802-022-00996-0
|View full text |Cite
|
Sign up to set email alerts
|

Social Anxiety and Suicidality in Youth: A Systematic Review and Meta-analysis

Abstract: Suicide is a leading cause of death among young people every year. Identifying risk factors provides opportunities to intervene, and social anxiety may represent one such factor. This systematic review and meta-analysis aimed to review the evidence of associations between social anxiety and suicidality in youth (10–25 years). Embase, PsycInfo, and Medline were searched to identify relevant articles. Meta-analysis was conducted to examine the mean effect sizes of concurrent and prospective associations between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…Anxiety symptoms were also identi ed as a signi cant risk factor for both suicidal ideation and severity of suicidal ideation. This association is consistent with the existing literature on the comorbidity between anxiety and suicidal ideation in adolescents [13,40,41]. A study involving 7054 adolescents, with an average age of 15.8 years, found a signi cant association between generalized anxiety symptoms and suicidal ideation [42].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Anxiety symptoms were also identi ed as a signi cant risk factor for both suicidal ideation and severity of suicidal ideation. This association is consistent with the existing literature on the comorbidity between anxiety and suicidal ideation in adolescents [13,40,41]. A study involving 7054 adolescents, with an average age of 15.8 years, found a signi cant association between generalized anxiety symptoms and suicidal ideation [42].…”
Section: Discussionsupporting
confidence: 91%
“…Another cross-sectional study, conducted among senior high school students, revealed a moderate correlation between anxiety symptoms and suicidal ideation [43]. Moreover, a systematic review and meta-analysis demonstrated a signi cant association between higher levels of social anxiety and more frequent occurrences of suicidal ideation [40]. Multiple multilevel analyzed studies have consistently highlighted a signi cant correlation between learning anxiety and suicidal ideation [44].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with suicidal behavior tend to hurt themselves before deciding to kill themselves. Research reveals suicidal behavior is closely related to low self-esteem, shame, hopelessness, feeling alone, stress and the presence of psychiatric disorders [3,13]. Suicidal behavior is also often associated with a state of individual trauma to something.…”
Section: Descriptivementioning
confidence: 99%
“…In addition to negative stress coping, another risk factor for suicidal behavior is psychiatric disorders. Psychiatric disorders such as major depression, bipolar disorder, personality disorders, and anxiety have been shown to be significantly associated with suicidal behavior [3].…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with social anxiety disorder report low quality of life and severe impairments in social, occupational, and educational functioning [ 6 , 7 ]. In addition, a recent meta-analysis of the relationship between social anxiety and suicide in youth showed that higher levels of social anxiety were associated with more frequent suicidal ideation and higher current suicidal risk [ 8 ]. Given the harmfulness of social anxiety, it is necessary to investigate its mechanism and formulate timely intervention measures for college students with social anxiety.…”
Section: Introductionmentioning
confidence: 99%